Public Opinions on Inter-Korean Economic Cooperation: A Survey Analysis - Seung-Ho Jung; Yong-Shin Cho (KDI Journal of Economic Policy, 2021)
This research attempts to provide an in-depth analysis of the public perceptions of inter-Korean economic cooperation. KDI survey data with a sample size of 1,000 were subjected to empirical analyses. By means of ordered logit estimations, we derive the following results. First, there is a significant effect of age on economic cooperation perceptions, where younger generations tend to be more negative. Second, the group who has positive view on the economic cooperation tends to prefer large-scale, domestic-entity-funded cooperation projects, whereas the group who has negative view tends to prefer small-scale projects and projects funded by international organizations. According to these results, prioritizing trade with the involvement of international organizations is likely to be an effective measure to alleviate potential political constraints and to achieve sustainable long-run economic cooperation systems when pursuing the economic cooperation.
Keywords: H77; F55; 330; Inter-Korean Economic Cooperation; Public Support; Policy on North Korea; Financing